Competition with Exclusive Contracts and Market-Share Discounts - Calzolari, Giacomo; Denicolò, Vincenzo (American Economic Review, 2013)
We analyze firms that compete by means of exclusive contracts and market-share discounts (conditional on the seller's share of customers' total purchases). With incomplete information about demand, firms have a unilateral incentive to use these contractual arrangements to better extract buyers' informational rents. However, exclusive contracts intensify competition, thus reducing prices and profits and (in all Pareto undominated equilibria) increasing welfare. Market-share discounts, by contrast, produce a double marginalization effect that leads to higher prices and harms buyers. We discuss the implications of these results for competition policy. (JEL D43, D83, D86, K21, L14, L42)